Switching Current Density of Perpendicular Magnetization by Spin-Orbit Torque - Zhu, Lijun; Ralph, D. C.; Buhrman, R. A. (2021 IEEE 32nd Magnetic Recording Conference (TMRC), 2021)
In-plane current-induced strong dampinglike spin-orbit torque (SOT) can enable sub-nanosecond switching of thin-film nanomagnets for nonvolatile magnetic storage [1] . Enormous efforts have been made on developing energy-efficient, high-endurance, integration-friendly spin current generators (SCGs) [2] , [3] that can provide high dampinglike SOT efficiency \left( {ξ _{DL}^j} \right) . This is mainly motivated by the fact that ξ _{DL}^j of a SCG/ferromagnet (FM) heterostructure directly connects to the density of the critical switching current inside the SCG layer ( j c ) and thus the total switching current ( I c , the sum of the currents in the SCG and the FM layers) that will define the energy efficiency \left( { \propto I_{\text{c}}^2} \right) , the scalability (the transistor dimension ∝ I c ), and the endurance (electro-immigration \propto I_{\text{c}}^2 ) of spin-orbit torque magnetic tunnel junctions (SOT-MTJs).